Громадсько-політична активність української інтелігенції Волині у 20-30-х роках ХХ ст. (історико-правовий аспект) - Булавіна, С.; Марківська, Л.; Bulavina, S.; Markivska, L. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті досліджено історико-правовий аспект формування моделей та шляхів громадсько- політичної активності української інтелігенції Волині у 20- 30-х роках ХХ століття. Проведено аналіз факторів, які визначили провідну роль національної інтелігенції краю у процесі державотворення, творення політичних партій та громадських організацій. У міжвоєнний період українська інтелігенція Волині використовувала всі можливі політичні засоби боротьби за своє визволення – від парламентських – до збройних. Опозиція польським урядовим асиміляційним намірам склала головний компонент політичного кредо волинської інтелігенції.The article provides historical-legal analysis of the public and political activity of the Ukrainian intelligentsia in Volyn in the 20-30-ies of XX cent. The author claims that the mode of life of this social group in the interwar period was predetermined by the peculiarities of the political status of the province and chauvinistic policy of the Polish government with regard to the Ukrainian population. The most important aspects and models of Volyn intelligentsia national identity formation and activities of the political parties analyzed in the article shed light on the role of the political movements which gave rise to the stratification process among the Ukrainian intelligentsia in accordance with the political beliefs: communist, represented by the Communist Party of Western Ukraine; nationalist movement under the leadership of the Ukrainian Nationalists Organization; national-democratic, headed by the Ukrainian national-democratic union. On the political arena, besides the aforementioned, in the second half of the 30-ies of XX century there appeared a new right-wing radical organization - the National Unity Front. It has been concluded that Volyn Ukrainian intelligentsia used all possible political means of struggle for emancipation - from the parliamentary to the military ones (terrorist activity of CPWU, OUN).
Public and Political Activity of the Ukrainian Intelligentsia in Volyn in the 20-30-ies of XX Cent. (Historical and Legal Aspects).
Keywords: інтелігенція; українсько-польські відносини; громадсько-політична активність; політичні організації; Волинь; intelligentsia; the Ukrainian-Polish relations; social and political activity; political organizations; Volyn